2010
DOI: 10.1111/j.1559-1816.2010.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Sacred Violations, Perceptions of Injustice, and Anger in Muslims

Abstract: Anger has been at the center of religiopolitical conflicts and has been associated with well‐being. This study examined the role of Muslim anger in sociopolitical events perceived as a sacred violation. A Muslim sample (N = 151) identified adverse political events that have deeply affected them; and completed measures of anger, sacred violations, perceptions of injustice, and religiousness. Sacred violations and perceptions of injustice were associated with greater levels of anger, with sacred violations being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…To date, research on American Muslims has examined how anti-Muslim sentiments and societal stereotypes affect American Muslims’ religious coping (e.g., Abu-Raija et al, 2010; Brown et al, 2010), youth identity formation (e.g., Fine and Sirin, 2007) and emotions in response to the 10-year anniversary of 9/11 (Rodriguez Mosquera et al, 2013). The future of psychology as an inclusive discipline lies in expanding its theories and methods to include under-studied cultural, ethnic, gender, and religious communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research on American Muslims has examined how anti-Muslim sentiments and societal stereotypes affect American Muslims’ religious coping (e.g., Abu-Raija et al, 2010; Brown et al, 2010), youth identity formation (e.g., Fine and Sirin, 2007) and emotions in response to the 10-year anniversary of 9/11 (Rodriguez Mosquera et al, 2013). The future of psychology as an inclusive discipline lies in expanding its theories and methods to include under-studied cultural, ethnic, gender, and religious communities.…”
Section: Discussionmentioning
confidence: 99%
“…This study is novel as previous research on American Muslims has mainly focused on youth identity formation (e.g., Fine and Sirin, 2007; Sirin et al, 2010); religious coping (e.g., Abu-Raija et al, 2010; Brown et al, 2010); and emotions about the 10-year anniversary of 9/11 (Rodriguez Mosquera et al, 2013). Furthermore, sadness has typically been examined in the context of grief and bereavement (Bonanno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In their study of a community sample, Pargament et al (2005) found that people who perceived their negative Ufe events to be violations of the sacred reported more intrusive thoughts and greater anger and less post-traumatic growth. Other studies on desecration also show that perceptions of sacred violation have negative ties to health and weU-being (e.g.. Brown et al 2010;Kjumrei et al 2009;Mahoney et al 2002). For example, working with a community sample of divorced adults, Krumrei et al (2009) examined the role of three spiritual responses to divorce for psychological adjustment, one of which is desecration.…”
Section: Desecrationmentioning
confidence: 93%
“…The more they recaUed that they experienced their parents' divorce as desecration (and sacred loss), the more they reported current depression, anxiety, and painful feelings about the divorce, including heightened paternal blame, self blame, loss and abandonment, seeing Ufe through the filter of divorce, and intrusive thoughts (Warner et al 2008). Brown et al (2010) worked with a sample of 151 Canadian MusUms to examine MusUm anger in response to sociopolitical events perceived as a sacred violation. They found that sacred violations and perceptions of injustice were associated with greater levels of anger, with sacred violations being the stronger predictor.…”
Section: Desecrationmentioning
confidence: 99%
“…Inventories recording differential exposure to stressful political events within protracted political conflicts and crises have also been used with adults (e.g., Muldoon & Downes, ; Muldoon, Schmid, & Downes, ). Brown, Abernethy, Gorsuch, and Dueck () interviewed an ethnically diverse sample of Muslims residing in Toronto (Canada) area and asked them about 20 present‐day adverse political events that might have affected them personally (i.e., direct exposure), affected someone they knew, or that they became aware of via media reports (i.e., vicarious exposure). The events ranged in severity and discreteness (or chronicity), and included, for example, body searches at airports, hostility toward traditional Islamic dress, insolent religious cartoons, desecration of the Qur'an, or ongoing Israeli–Palestinian conflict.…”
Section: Stressors Associated With Political Violence and Oppressionmentioning
confidence: 99%